HACCP and ISO 22000 application to foods of animal origin - Arvanitoyannis, Ioannis S. (Wiley-Blackwell, 2009)
"Food safety is an increasingly important issue. Numerous food crises have occurred internationally in recent years (the use of the dye Sudan Red I; the presence of acrylamide in various fried and baked foods; mislabeled or unlabelled genetically modified foods and the outbreak of variant Creutzfeldt-Jakob disease) originating in both primary agricultural production and in the food manufacturing industries. Public concern at these and other events has led government agencies to implement a variety of legislative actions covering many aspects of the food chain." "This book presents and compares the HACCP and ISO 22000:2005 food safety management systems. These systems were introduced to improve and build upon existing systems in an attempt to address the kinds of failures that can lead to food crises. Numerous practical examples illustrating the application of ISO 22000 to the manufacture of food products of animal origin are presented in this extensively-referenced volume. After an opening chapter, which introduces ISO 22000 and compares it with the well-established HACCP food safety management system, a summary of international legislation relating to safety in foods of animal origin is presented. The main part of the book is divided into chapters that are devoted to the principle groups of animal-derived food products: dairy, meat, poultry, eggs and seafood. Chapters are also included on catering and likely future directions." "The book is aimed at food industry managers and consultants, government officials responsible for food safety monitoring, researchers and advanced students interested in food safety."--BOOK JACKET.